1987
DOI: 10.1002/cber.19871201022
|View full text |Cite
|
Sign up to set email alerts
|

Elektronentransferreaktionen nichtalternierender chinoider und hydrochinoider Verbindungen Verhalten von 5,12‐Dimethoxynaphth[2,3‐a]azulen bei der Oxidation1)

Abstract: Chirai 5,5',19,12'-tetramethoxy-l 1,ll'-binapbth-(2,3-a]azt~lcne (3a) is formed by oxidative coupling of Za with iron(l1l) chloride in dimethylfonnamide. The reaction of 2a with tropylium tetrafluoroborate (8), triphenylcarbenium salts 7, or trichlorwyclopropenylium tetrachloroaluminate (9) yields either biazulene 3a or electrophilic substitution at C-11, depending on the specific reaction conditions. In case of Za and 8 the azulenium lob, formed in the primary step, is transformed into 11 by reaction with tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…As an application of this method, the reaction of 1‚AlCl 4with 3 equiv of naphth[2,3-a]azulene 6 gave cation 7, having the longest-wavelength absorption at 592 nm, in 42% yield (eq 2). 10 A derivative of tris(2-thienyl)cyclopropenylium cation 9 was prepared in 37% yield by a similar reaction with thienylphenol 8 and was transformed into dianion 10 with a highly delocalized π-system, having the longest-wavelength absorption at 693 nm (eq 3). 11 This method is effective particularly for the reaction with activated π-systems.…”
Section: A Cations Having Carbon and Silicon Substituentsmentioning
confidence: 99%
See 1 more Smart Citation
“…As an application of this method, the reaction of 1‚AlCl 4with 3 equiv of naphth[2,3-a]azulene 6 gave cation 7, having the longest-wavelength absorption at 592 nm, in 42% yield (eq 2). 10 A derivative of tris(2-thienyl)cyclopropenylium cation 9 was prepared in 37% yield by a similar reaction with thienylphenol 8 and was transformed into dianion 10 with a highly delocalized π-system, having the longest-wavelength absorption at 693 nm (eq 3). 11 This method is effective particularly for the reaction with activated π-systems.…”
Section: A Cations Having Carbon and Silicon Substituentsmentioning
confidence: 99%
“…As an application of this method, the reaction of 1 ·AlCl 4 - with 3 equiv of naphth[2,3- a ]azulene 6 gave cation 7 , having the longest-wavelength absorption at 592 nm, in 42% yield (eq 2) …”
Section: Synthesis Of Cyclopropenylium Cationsmentioning
confidence: 99%
“…The irreversible wave represents a two-step process involving a one-electron oxidation of the DHA subunit followed by a chemical step (EC-type mechanism) leading to a significant change in the molecular structure. Since polyenic radical cations have a preference for dimerization,' 34 ' it is reasonable to speculate on the formation of the dirneric dication species as shown in structure 41. The chemical reversibility of this EC-type process was confirmed by multisweep thin layer experiments.…”
Section: Molecular Switches Based On Dihydroazulene-vinylheptafulvenementioning
confidence: 99%
“…Hence, azulene possesses donor-acceptor characteristics that may be exploited in advanced functional electronic, optoelectronic, and electrochromic devices. Among azulene derivatives, expansion of the π-conjugated system of 1,1'-biazulene derivatives has attracted significant interest owing to their unique spectral and redox properties [1][2][3]. In that context, we recently reported that azulene-fused helicenes could be formed through 1-functionalized [5]helicenes by Pt(II)-catalyzed cycloisomerization [4,5].…”
mentioning
confidence: 98%
“…Its crystal structure and electrochemical properties are also reported. 10,phenanthrene (2) 10-Methoxyazuleno[2,1-c]phenanthrene (1) was synthesized according to our previously reported method [3]. Under an argon atmosphere, a mixture of compound 1 (50 mg, 0.16 mmol) and APS (183 mg, 0.80 mmol) in degassed toluene (25 mL) was heated at 100 °C for 1 h. Additional APS (183 mg, 0.80 mmol) was added and the mixture was stirred for 2 h at 100 °C.…”
mentioning
confidence: 99%